2005
DOI: 10.1038/sj.bjc.6602490
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of antihypertensive treatments and risk of renal cell cancer

Abstract: We studied 335 682 county residents, of whom 113 298 had been prescribed antihypertensive treatment (AHT), in the period 1989 -2002 in North Jutland County, Denmark to examine the relation between different AHTs and the risk of renal cell carcinoma (RCC). An internal comparison was performed among the different classes of AHT users with users of beta blockers as the reference, in order to address potential confounding and bias. The average follow-up was 10 years (range 0 -13). Use of any AHT was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 14 publications
1
32
2
5
Order By: Relevance
“…There is evidence that renal carcinoma is associated with diuretic use (Grossman et al, 2001), although this is not generally accepted (Choi et al, 2005;Fryzek et al, 2005). Prenatal exposure to diuretics was associated with an increased risk of childhood brain tumours (Preston-Martin et al, 1982), which could not be confirmed by subsequent studies (Kuijten et al, 1990;McCredie et al, 1994;McKean-Cowdin et al, 2003).…”
Section: Discussioncontrasting
confidence: 37%
“…There is evidence that renal carcinoma is associated with diuretic use (Grossman et al, 2001), although this is not generally accepted (Choi et al, 2005;Fryzek et al, 2005). Prenatal exposure to diuretics was associated with an increased risk of childhood brain tumours (Preston-Martin et al, 1982), which could not be confirmed by subsequent studies (Kuijten et al, 1990;McCredie et al, 1994;McKean-Cowdin et al, 2003).…”
Section: Discussioncontrasting
confidence: 37%
“…In two prospective studies, antihypertensive treatment was associated with higher risk of renal cell cancer (Fraser et al, 1990;Heath et al, 1997), but others found no association (Grove et al, 1991;Flaherty et al, 2005;Schouten et al, 2005). One large study linking prescriptions and cancer registration in Denmark indicated that antihypertensive medication may increase risk, but was interpreted as being due to confounding by underlying hypertension (Fryzek et al, 2005). One prospective study (Flaherty et al, 2005) and two case -control studies (Yuan et al, 1998;Shapiro et al, 1999) have also reported positive associations with a history of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In men, there was no association with blood pressure. The association of blood pressure with risk of renal cell cancer has been investigated in a number of cohort (Fraser et al, 1990;Grove et al, 1991;Coughlin et al, 1997;Heath et al, 1997;Chow et al, 2000;Choi et al, 2005;Flaherty et al, 2005;Fryzek et al, 2005;Lindgren et al, 2005;Schouten et al, 2005) and case -control (McLaughlin et al, 1995;Yuan et al, 1998;Shapiro et al, 1999) studies, using as principal exposure variable either recorded blood pressure or reported hypertension. In men, recorded blood pressure has shown a convincing exposure -response gradient related to renal cell cancer risk (Coughlin et al, 1997;Chow et al, 2000).…”
mentioning
confidence: 99%
“…Anti hipertansif ilaçların, özellikle de diüretiklerin proksimal tübül üzerine etkili olmaları ve BHK'nında daha çok buradan gelişmesi nedeniyle bu ajanların kullanımının BHK'nın potansiyel sebeplerinden olabileceği (25) ileri sürülmesine rağmen kanıtlanmamıştır (26). Literatürde bu konuda görüş birliği yoktur.…”
Section: Kan Basıncı Yüksekliğiunclassified